Leading by Design: Lessons for the Future From 25 Years of the Executive Leadership in Academic Medicine (ELAM) Program for Women. (October 2020) - Jagsi, Reshma; Spector, Nancy D.
Abstract : The Hedwig van Ameringen Executive Leadership in Academic Medicine (ELAM) Program for Women is designed to promote the careers of senior female leaders in academic health care in a way that ultimately seeks to transform culture and promote gender equity far beyond the careers of its participants. In an era of increased awareness of gender inequity within academic medicine, the longevity of the ELAM program raises several important questions. First, why is such a program still needed? Second, what exactly does it do, and what has been its influence on its participants and beyond? And third, what lessons can ELAM's example provide to help guide the medical profession as it strives to promote gender equity in the field? In this Invited Commentary, the authors seek to answer these questions from the perspective of a recent program participant and the current program director. The authors review the evidence that identifies how women, even today, face accumulating disadvantage over the course of their academic careers, stemming from repeated encounters with powerful unconscious biases and stereotypes, societal expectations for a gendered division of domestic labor, and still-present overt discrimination and sexual harassment. They describe ELAM's approach, which builds the knowledge and skills of the women who participate in the program, while also intentionally raising their visibility within their home institutions so that they have opportunities to share with institutional leaders what they have learned in ways that not only promote their own careers but also support gender equity in the broader environment. The authors conclude by offering thoughts on how ELAM's model may be leveraged in the future, ideally in partnership with the numerous professional societies, funding agencies, and other organizations that are committed to accelerating the rate of progress toward gender equity at all levels of academic medicine.